PENINGKATAN PRODUKTIVITAS PEMASARAN UMKM CATERING MPOK ATIEK DENGAN PENDEKATAN BUSINESS MODEL CANVAS DAN ANALISIS SWOT - Devi Lastina; Theresia Sunarni (Jurnal Ilmiah Dinamika Teknik, 2019)
Catering Mpok Atiek SME’s is one of the SME’s that is engaged in home catering business in the regency of Ogan Komering Ulu. Based on the results of observations and interviews conducted, it is known that the applied marketing strategy is not optimal, causing low levels of marketing, benefits and productivity of the marketing low, current marketing productivity is 1,4282. In formulating the right marketing strategy used business model canvas and SWOT analysis to identify and analyze strengths, weaknesses, opportunities, and threats to customer segments, value propositions, channels, customer Relationship, revenue streams, key resources, key activities, key partnerships, and cost structure owned by SME’s. Then the SWOT matrix is used to produce an improvement strategy. Tthe implementation of improvements included expanding the area of the order, conducting promotion (the sticker creation of business logos and advertising through Instagram) and optimizing production processes and services (addition of product variants, increase in the number of manpower, payment timing, addition of suppliers). Marketing productivity after the improvement implementation was 1.1580. From these data, there is an increase in marketing productivity by 6.94%. increase that occurs is not optimal because there are additional costs to be such as worker salaries and fees for the addition of food containers.